PENGARUH PENERAPAN PENDEKATAN LINGKUNGAN TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Ledina, Pelagia; Kresnadi, Hery; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to analyze the effectiveness of environmental approach implementation on towards IPA’s learning outcomes at grade V SDN 38 Pontianak Utara